Functionalized TiO2‑waste‑derived photocatalytic materials for emerging pollutant degradation : synthesis and optimization - Devagi, Kanakaraju; Pheodora Pamela, Natashya; Ying Chin, Lim; Ivy Tan, Ai Wei (Springer Nature, 2025)
Developing an effective, reusable photocatalyst that combines high photocatalytic efficiency with easy separation could significantly enhance the removal of organic pollutants. This study developed reusable photocatalysts by integrating TiO₂ with biomass-derived activated carbon (AC) and magnetite (Fe3O4) to enhance the removal of methylene blue (MB), acetaminophen (ACT), and their mixtures. Advanced microscopic and spectroscopic techniques, including FE-SEM, EDX, TEM, FTIR, XRD, and BET, were applied to identify the physicochemical properties of the composites. Both TiO2/AC-10%(436 m2/ g) and TiO2/AC/Fe3O4 (494 m2/g) exhibited high surface areas, suggesting a significant abundance of active sites for pollutant degradation. Optimization of operational parameters, including pollutant concentration, irradiation time, and composite dosage, was conducted via response surface methodology (RSM) with a Box-Behnken design (BBD), using TiO2/ AC-10%. Under optimized conditions, MB and ACT removal reached 98.37% and 87.28%, respectively within 120 min. The TiO2/AC/Fe3O4 composite maintained high efficiency over five reuse cycles. These waste-derived, magnetically separable photocatalysts offer a sustainable, efficient solution for organic pollutant removal in wastewater treatment.